Comment on: "A Paleogene ichnological record from the Wilcox Formation: Ophiomorpha and Venericardia (Venicor) zapatai in the Burgos Basin, northern Mexico" by M.I. Hernández-Ocaña, E. Chacon-Baca, S.A. Quiroz-Barroso, S. Eguiluz-de Antuñano, F. Torres-de la Cruz, and G. Chávez-Cabello. (March 2020) - Jenchen, Uwe
Abstract: In their 2019 paper, "A Paleogene ichnological record from the Wilcox Formation: Ophiomorpha and Venericardia (Venicor) zapatai in the Burgos Basin, northern Mexico, " Hernández-Ocaña et al. present a stratigraphic, sedimentological, and paleontological reconstruction of the Wilcox Fm. from a limited section located in the western part of the Burgos Basin. In my opinion, this paper contains a series of grave errors that puts in doubt the authors' correlation with the Eocene Wilcox Fm., determination of the species Venericardia (Venericor) zapatai, and stratigraphic interpretation of the described sequence.